Aspectos relevantes en la biología de Cetengraulis mysticetus (Günther) (Pisces: Engraulidae) en el Golfo de Nicoya, Costa Rica (ING) - Rodríguez, Jorge Arturo (1998)
Cetengraulis mysticetus is an American anchovy found on the Pacific coast between Mexico and Peru. The fecundity and the biometry relations were studied in the Gulf of Nicoya population, Costa Rica. The length of first sexual maturity was estimated to be 12.6 cm. The sex ratio was 1:1.2 male to female in the maximum spawning period. The total fecundity changed from 48,498 oocytes to 98,278 oocytes according to the total length size. The relative fecundity was estimated in two length-size groups, the first group (16-18,3 cm length) with 813 oocytes per gram fish and the second group (19-21,9 cm length) with 1,145 oocytes per gram fish. The biometric study shows differences only in dorsal length with total length size relation females are isometric and males are negative alometric. The other body relationships are equal in both male and female.